Heterodox Hegels: heresiology in de Lubac and Bulgakov - Coyle, Justin Shaun (Scottish journal of theology, 2020)
This paper considers two twentieth-century heresiological critiques of G. W. F. Hegel. That Henri de Lubac and Sergius Bulgakov should both worry at Hegel's heresy' is hardly surprising. More surprising, however, is how and that each charges Hegel with a different heresy. Though de Lubac's heresiological critique has proven more influential, I commend Bulgakov's. The paper concludes by querying the very strategy of assaying philosophers like Hegel heresiologically.